2014
DOI: 10.1097/meg.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of hepatitis D in Pakistani children

Abstract: Children with HDV infection have more aggressive liver disease than HBV monoinfection irrespective of HBeAg status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We previously reported that children with HDV infection have a more aggressive form of liver disease than those with HBV monoinfection [10]. This was observed irrespective of HBeAg status.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously reported that children with HDV infection have a more aggressive form of liver disease than those with HBV monoinfection [10]. This was observed irrespective of HBeAg status.…”
Section: Discussionmentioning
confidence: 81%
“…Cirrhosis was seen in 13 (27%) cases with hepatitis D compared with two (4%) with hepatitis B monoinfection. Six patients with hepatitis D had decompensation at the time of presentation, whereas only one patient with HBV monoinfection had decompensation [10].…”
Section: Introductionmentioning
confidence: 97%
“…Despite this, alanine aminotransferase (ALT) was elevated in almost all patients and there was no difference in the severity of disease in HBeAg-reactive and HBeAg-nonreactive HDV patients. Indeed, of the six patients with decompensation, five were HBV DNA positive [ 58 ]. Moreover, HDV-infected children in this study progressed to significantly worse outcomes than those with HBV mono-infection alone (matched controls).…”
Section: Reviewmentioning
confidence: 99%
“…In Mauritania, HDV co-infection worsens liver disease, both clinically and biologically, as confirmed by the APRI and FibroMeter tests. These tests may be useful for the management of delta hepatitis, which is a major health problem in Mauritania (40).…”
Section: Mauritaniamentioning
confidence: 99%